Evaluation of association of demographic profiles and sero prevalence of HBV and HCV among the patients presenting with chronic liver disease and its complications: A Tertiary Care Hospital Based Study - Richmond Ronald Gomes; Md. Akmat Ali (Open Journal of Hepatology - Peertechz Publications, 2020)
Background: Now-a-days chronic liver disease is one of the major health problems in the world. In developing countries, chronic liver disease due to hepatitis virus (like hepatitis B and hepatitis C virus) is increasing day by day. It is rapidly emerging as a major health problem. So the present study was conducted to document the hepatitis B and hepatitis C virus in patient with chronic liver disease by an easy and simple marker like HBsAg, Anti HBc (total) and Anti HCV in a tertiary hospital.  Methods: Serum samples were collected from 100 selected cases who were diagnosed as a case of chronic liver disease in medicine and gastroenterology department of DMCH. Study period was from April 01, 2016 to September 30, 2018. For detection of HBsAg, Anti HBc (total) and Anti HCV, Immunochromatographic Test (ICT) was done in every case.  Results: Out of 100 cases, HBsAg seropositive with negative Anti HCV was found in 64% cases, Anti HCV positive with negative HBsAg was found in 16% cases, both HBsAg and anti HCV positive was found in 4% cases, both HBsAg and anti HCV negative was found in 16% cases. Among these cases, 74% were male and 26% were female. Here male: female was 3:1 and among them, 75% male was seropositive for either HBsAg or Anti HCV.  Conclusion: The high frequency of seropositivity in patients with chronic liver disease with male predominance is found in tertiary care settings. The number of Anti HCV seropositive patient indicates that it is an emerging health problem in our country.